The GIY-YIG Type Endonuclease Ankyrin Repeat and LEM Domain-Containing Protein 1 (ANKLE1) Is Dispensable for Mouse Hematopoiesis. - Juliane Braun; Arabella Meixner; Andreas Brachner; Roland Foisner (PLoS ONE)
Ankyrin repeat and LEM-domain containing protein 1 (ANKLE1) is a GIY-YIG endonuclease with unknown functions, mainly expressed in mouse hematopoietic tissues. To test its potential role in hematopoiesis we generated Ankle1-deficient mice. Ankle1Δ/Δ mice are viable without any detectable phenotype in hematopoiesis. Neither hematopoietic progenitor cells, myeloid and lymphoid progenitors, nor B and T cell development in bone marrow, spleen and thymus, are affected in Ankle1Δ/Δ-mice. Similarly embryonic stress erythropoiesis in liver and adult erythropoiesis in bone marrow and spleen appear normal. To test whether ANKLE1, like the only other known GIY-YIG endonuclease in mammals, SLX1, may contribute to Holliday junction resolution during DNA repair, Ankle1-deficient cells were exposed to various DNA-damage inducing agents. However, lack of Ankle1 did not affect cell viability and, unlike depletion of Slx1, Ankle1-deficiency did not increase sister chromatid exchange in Bloom helicase-depleted cells. Altogether, we show that lack of Ankle1 does neither affect mouse hematopoiesis nor DNA damage repair in mouse embryonic fibroblasts, indicating a redundant or non-essential function of ANKLE1 in mouse.